PROFIL TEKNIK DASAR TIM BOLA VOLI PUTRI KABUPATEN KUANTAN SINGINGI DI MASA PANDEMI COVID-19 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The development and coaching of volleyball achievements in Kuantan Singingi Regency has become a problem since the covid 19 pandemic, the women's volleyball team of Kuantan Singingi Regency rarely carries out routine training activities, so it is feared that this can reduce the quality of the game owned by the women's volleyball team. Since 2020 Kuantan Singingi athletes and coaches have undergone a change in the coaching process, due to an epidemic that has attacked the whole world including Indonesia, namely the Covid-19 pandemic (corona virus disease 2019), therefore it is necessary to review the basic technical profile of the volleyball team daughter of Kuantan Singingi Regency during the covid-19 pandemic?. Therefore, this study was conducted with the aim of knowing the basic technical profile of the women's volleyball team in Kuantan Singingi Regency during the COVID-19 pandemic. The type of research used is descriptive using survey methods, with data collection techniques using test and measurement techniques. The data in this study were the entire population of 20 people with a test instrument, namely a volleyball skill test (service test, top passing test, bottom passing and smash test). Based on data collection and data processing techniques, the raw scores obtained through the volleyball playing skill test were converted into T scores and then interpreted into volleyball skills test norms with the AAHPERD Volleyball Test Norms assessment standard, it was found that the basic technical profile of the district women's volleyball team Kuantan Singingi during the covid-19 pandemic got an average t score of 49.84 which was included in the Medium categoryKey Words: Basic Technical Profile of Women's Volleyball Team, Covid-19